Pengaruh Lumpur Laut pada Tanah Gambut untuk Media Tanam Kedelai terhadap Sifat Kimia Tanah dan Emisi CO2 - Yenni, Yenni; Sagiman, Saeri; Susana, Rini (Perkebunan dan Lahan Tropika, 2023)
This study aimed to determine the effect of coastal sediment on peat soil for soybean planting medium to soil chemical properties and CO2 emissions. The research lasted for 3 months starting from preparation to presentation of the results. This research was conducted at the Laboratory of Soil Quality and Health, Laboratory of Chemistry and Soil Fertility and in the Faculty of Agriculture experimental garden Tanjungpura University. The method used is experiment with a completely randomized design (CRD), which consists of 5 treatments and 4 replications. Each polybag contained 1 plant sample. So the number of plants altogether 20 units of the plant. Treatment as follows: LL0 : Without treatment coastal sediment, LL1 : coastal sediment 25.2 tonnes/ha equivalent to 180 g/polybag, LL2 : coastal sediment 33.6 tonnes/ha equivalent to 240 g/polybag, LL3 : coastal sediment 42 ton / ha equivalent to 300 grams/polybag, LL4 : coastal sediment 50.4 tonnes/ha equivalent to 360 g/polybag. The variables observed in this study are soil pH, cation exchange capacity (CEC), Base Saturation, C/N, CO2 emissions and the dry weight of soybean. The results showed that application   of coastal sediment with various doses on peat soil can increase soil pH, Base Saturation and C/N ratio, with decreasing CEC. There is just a little correlation of costal sediment on CO2 emissions of soil (R2=0.0009). Coastal sediment 33.6 tonnes/ha equivalent to 240 grams/polybag was resulted dry weight of soybean   to maximum vegetative phase.